2014
DOI: 10.3168/jds.2014-8208
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal metabolism of phytoestrogens in lactating dairy cows fed silages with different botanical composition

Abstract: Dietary phytoestrogens are metabolized or converted in the gastrointestinal tract of ruminants, only limited knowledge exists on the extent and location of this conversion in vivo. The objective of this study was to quantify the gastro-intestinal metabolism of phytoestrogens in lactating dairy cows fed silages with different botanical composition. Four lactating rumen cannulated Norwegian Red cattle were assigned to a 4 × 4 Latin square with 1 cow per treatment period of 3 wk. The 4 treatment silages were prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
58
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 52 publications
(113 reference statements)
6
58
1
2
Order By: Relevance
“…Some authors have pointed out the high concentration of enterolactone in milk rather than its low uptake (Steinshamn et al, 2008;Petit et al, 2009). Njastad et al (2014) have recently reported that factors such as reconjugation and secretion into the rumen and intestinal wall as well as in cells from the udder could be limiting factors in the content of dietary isoflavones and lignans into milk. ABCG2 has been previously reported to be involved in intestinal conjugation and hepatic metabolism of isoflavones (Alvarez et al, 2010).…”
Section: Enterolactonementioning
confidence: 99%
“…Some authors have pointed out the high concentration of enterolactone in milk rather than its low uptake (Steinshamn et al, 2008;Petit et al, 2009). Njastad et al (2014) have recently reported that factors such as reconjugation and secretion into the rumen and intestinal wall as well as in cells from the udder could be limiting factors in the content of dietary isoflavones and lignans into milk. ABCG2 has been previously reported to be involved in intestinal conjugation and hepatic metabolism of isoflavones (Alvarez et al, 2010).…”
Section: Enterolactonementioning
confidence: 99%
“…The main metabolism of phytoestrogens occurred in the rumen and the main route of excretion was through feces and urine, with only a small part being excreted in milk. The concentration of phytoestrogens in milk can be manipulated through intake but the intermediate transfer capacity to milk appears to be limited by saturation [66].…”
Section: Characterization Of Cow Dung For Farming Systemmentioning
confidence: 99%
“…The markers Cr and Yb in reticular contents and feces were analyzed in an atomic absorption spectrophotometer (GBC SavantAA Ser. No A6990; GBC Scientific Equipment, Hampshire, IL, USA) as described by Njåstad et al (2014).…”
Section: Grass-clover Silages and Experimental Dietsmentioning
confidence: 99%